Krylov subspace methods principles and analysis - Liesen, Jorg.; Strakos, Zdenek (Oxford : Oxford University Press, 2013)
This volume describes the principles and history behind the use of Krylov subspace methods in science and engineering. The outcome of the analysis is very practical and indicates what can and cannot be expected from the use of Krylov subspace methods challenging some common assumptions and justifications of standard approaches.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Iterative methods (Mathematics)